Mirror neurons, birdsong and human language: a hypothesis - Levy, Florence (Frontiers in Psychiatry, 2012)
Abstract The Mirror System Hypothesis (MSH) and investigations of birdsong are reviewed in relation to the significance for the development of human symbolic and language capacity, in terms of three fundamental forms of cognitive reference: iconic, indexical, and symbolic. Mirror systems are initially iconic but can progress to indexal reference when produced without the need for concurrent stimuli. Developmental stages in birdsong are also explored with reference to juvenile subsong vs complex stereotyped adult syllables, as an analogy with human language development. While birdsong remains at an indexal reference stage, human language benefits from the capacity for symbolic reference. During a pre-linguistic ‘babbling’ stage, recognition of native phonemic categories is established, allowing further development of a subsequent prefrontal and linguistic circuits for sequential language capacity.